Association of Vitamin D Deficiency and Degree of Coronary Artery Disease in Cardiac Patients with Type 2 Diabetes. (2nd November 2017) - Dziedzic, Ewelina A.; Gąsior, Jakub S.; Pawłowski, Mariusz; Dąbrowski, Marek
Abstract : Several modifiable factors may influence cardiac function in diabetic patients. The aim of the study was to evaluate the influence of vitamin D level on the stage of coronary atherosclerosis in cardiac patients diagnosed with type 2 diabetes. The study was performed in 337 consecutive patients undergoing coronarography. The stage of atherosclerosis was evaluated using Coronary Artery Surgery Study Score. The plasma 25(OH)D concentration was determined by an electrochemiluminescence method. Patients without significant lesions in coronary arteries presented the highest 25(OH)D level, significantly higher than patients with one-, two-, and three-vessel coronary artery disease (CAD) (p < 0.01 ). Significantly lower level of the 25(OH)D was observed in patients hospitalized due to acute coronary syndrome (ACS) in comparison to patients hospitalized due to stable CAD (p < 0.001 ). Lower 25(OH)D levels were observed in patients with the history of myocardial infarction (MI) in comparison to patients without previous MI (p < 0.001 ). In cardiac patients with diabetes, the higher number of stenotic coronary arteries is associated with lower values of the 25(OH)D. A group of male cardiac patients with diabetes with significant stenosis in three coronary arteries, hospitalized due to acute coronary syndrome, with a history of previous MI and hyperlipidemia presented the lowest vitamin D level.